2022
DOI: 10.3389/fpubh.2022.930208
|View full text |Cite
|
Sign up to set email alerts
|

HIV pre-exposure prophylaxis during the SARS-CoV-2 pandemic: Results from a prospective observational study in Germany

Abstract: AimsSince 2017, HIV pre-exposure prophylaxis (PrEP) care has been provided through an intersectoral collaboration at WIR (Walk-in-Ruhr, Center for Sexual Health and Medicine, Bochum, Germany). The aim of this study was to establish possible impact of COVID-restrictions on the sexual behavior of PrEP users in North Rhine-Westphalia.MethodsThe current PrEP study collected data of individuals using PrEP, their sexual behavior and sexually transmitted infections (STIs) before (each quarter of year 2018) and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
2
4
1
1
Order By: Relevance
“…The higher level of retention observed in our center compared with previous studies did not appear to be explained by differences in participants’ characteristics. As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The higher level of retention observed in our center compared with previous studies did not appear to be explained by differences in participants’ characteristics. As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
“…As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ]. Patients in our study showed a high (67%) but not unusual level of STI history; rates reported elsewhere ranged from 31% to 76% [ 2 , 17 , 22 , 24 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations